Tettigoniinae (Orthoptera: Tettigoniidae) from South-West of Turkey, with an incognito new species and comments on the genus Eupholidoptera - Ünal, Mustafa; Gorochov, Andrei V. (Zootaxa, 2024)
Twenty species are recorded from SW of Turkey. One new species, Eupholidoptera abscondita sp. nov., is described. An overlooked previous synonym of Eupholidoptera tucherti Harz, 1988 with E. krueperi (Ramme, 1930) is confirmed and Eupholidoptera helina Çıplak, 2009 is synonymized with E. smyrnensis (Brunner von Wattenwyl, 1882). Twenty-one Eupholidoptera species from Turkey and the Middle East are compared with images of the female subgenital plates.